Czesi i Rosjanie wobec organizacji polskich formacji wojskowych we wschodniej Rosji i na Syberii w 1918 roku - Wiśniewski, Jan (Fides, Ratio et Patria. Studia Toruńskie, 2018)
With the liberation of Czech and Slovak Siberia, Ural and Volga by the legionnaires, Polish military-political organizations began to be formed in individual cities in this area. The first such organization was established in June 1918 in Samara, one month after the Czechoslovak legion. Other organizations began to be established in such cities as Omsk, Novonikolevysk (now Novosibirsk), Ufa, Tomsk, Chelyabinsk, and Irkutsk. They joined the creation of their own military units. The Czechoslovak commanders were very keen to see Polish units in their army, chich helped the few - in relation to the needs and huge spaces – their own troops. Polish troops directed directly to the battle against the Bolsheviks in the summer of 1918 counted nearly half a thousand soldiers armed with rifles and machine guns, Chile during the training tere were about two thousand soldiers. In mid-July 1918, a meeting of representatives of Polish political organizations took place in Omsk. In the course of the discussion, a central organ – the Polish War Committee – was established, chich concluded an agreement with the Czechoslovak authorities, providing help to the Polish troops forming by the Czechoslovak authorities and troops. Under this agreement, the Polish formations were to be subordinated to the Czechoslovak command. This situation prevailed until January 1919, when Polish troops were subordinated to the command of allied forces in Siberia, with the arrival of General Pierre Maurice Janin in Siberia to France.